Una aproximación teórica a la ilusión del control y de la importancia de la (des) confianza en las alianzas estratégicas - Velasquez Salazar, Germán (2021)
This research aims to explain the effects of the participation of trust and distrust, as independent characteristics of the control mechanisms decided by the governance policies of the firms and generated by the desire for control of the firms. Our review of the literature has identified that there is no clarity on the influence of trust or distrust between firms as control mechanisms aimed at achieving the objectives of a strategic alliance.